A Feminist Approach to Masculinity and Femininity: Self-Vanity and Self-Confirmation in Virginia Woolf's To The Lighthouse (The Peerian Journal, 2024)
This paper employs a descriptive-analytical approach and provides a feminist critical analysis of Virginia Woolf's To the Lighthouse. It investigates the social mores and racial characteristics of Western civilization especially in British society. By concentrating on gender roles and societal norms, it also explores the social interactions between men and women in British culture. Even though the story takes place between two waves of feminism, various discrepancies, and misunderstandings have been identified between men and women as selfimprovement. Both look at the socioeconomic position of women from a feminist standpoint. To the Lighthouse depicts a patriarchal Western civilization generally and British specially that harbors several discriminatory attitudes against women. However, each wave of feminism represents a certain perspective about men's dominance over women suffrage. Therefore, women suffer from male hegemonies and oppression and subordination, which is backed by societal cultural standards, particularly in British cultures. The social structures and cultural norms in Western communities equally repress the rebellious women against the injustice and enslavement of a male-dominated society. One of the societal issues that both genders experience into the Lighthouse is class strife. Virginia Woolf made a significant contribution to modernizing English literature. During that period, Woolf backed the feminist cause and invented the stream-ofconsciousness writing approach to deal with people inner feeling. Finally, this study concludes that the stereotyped representations of the superior male and inferior woman in the novel are the same as those seen in British societies